Studi Kualitas Hadis terhadap Kedudukan Basmalah pada Surah al-Fatihah - Muhammad Irfan (STAIN Majene, 2022)
Abstract: This study wants to reveal the quality of the hadith about “Basmalah which is one of the verses of the letter al-Fatihah”. It is library research. The quality of the hadith is revealed through the hadith criticism method with the standard rules of hadith validity. The literature used is the takhrij hadith books, hadith books, biographies of hadith narrators, and books that contain the rules of hadith validity and hadith criticism methods. In this study, it was found that there were breaks of the sanad and weak narrators by hadith critics, so this hadith was judged weak. The study on matan of hadith was not carried out because one of the conditions for conducting criticism of matan was sahih or valid in the hadith sanad. Keywords: Basmalah, al-Fatihah, Hadith Quality Abstrak Dalam artikel ini peneliti ingin mengungkap kualitas hadis tentang “basmalah adalah salah satu ayat dari surat al-Fatihah”. Penelitian ini adalah penelitian kepustakaan. Kualitas dari hadis tersebut diungkap menggunakan metode kritik hadis dengan standar kaidah kesahihan hadis. Literatur yang digunakan adalah kitab (buku) takhrij hadis, kitab hadis, kitab biografi para periwayat hadis, dan kitab yang memuat kaidah kesahihan hadis dan metode kritik hadis. Dalam penelitian ini ditemukan bahwa terdapat keterputusan dalam sanadnya dan terdapat periwayat yang dinilai lemah (bermasalah) oleh kritikus hadis, sehingga hadis ini dihukumi lemah. Adapun penelitian matan hadis tidak dilakukan sebab salah satu syarat melakukan kritik matan adalah sanad hadis berstatus sahih. Kata kunci: Basmalah, al-Fatihah, Kualitas Hadis.